SISTEM PAKAR PENDIAGNOSA PENYAKIT KARIES PADA GIGI MENGGUNAKAN FUZZY INFERENCE SYSTEM DENGAN METODE TSUKAMOTO - , ST. HAJRAH MANSYUR, Dra. Sri Hartati, Msc, Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Particular dental problems cavities is still a serious problem in Indonesia. Health ministry data says nearly 80% of Indonesia's population experienced dental caries. From the survey also revealed only 38% of students who maintain good diet, 37% visited the dentist every six months, and 60% had dental caries. During this time there have been several methods to diagnose and determine the level of disease risk, especially in the form of an expert system. In this study an expert system to diagnose caries using Fuzzy Inference System with Tsukamoto method for determining the risk of disease that may be suffered by the patient. Input is needed is a symptom and clinical characteristics found in the teeth by the patient. Knowledge base designed using production rules (IF-THEN). Estimated value hypothesis (fire strength) obtained in each fuzzy rule for each disease on the basis of knowledge, then composed using a weighted average (weighted averange defuzzifier). The average yield is the weighted output caries risk.